PEMBELAJARAN SOSIAL-EMOSIONAL SEBAGAI STRATEGI REDUKSI PERILAKU PERUNDUNGAN DI SEKOLAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying in elementary schools is a serious problem that negatively impacts students’ social-emotional development and academic achievement. This study aims to analyze the effectiveness of Social-Emotional Learning (SEL) as a strategy to reduce bullying behavior in the school environment. The method used was a systematic literature review, analyzing 13 SINTA-indexed journal articles and 3 relevant reference books. The findings indicate that SEL is effective in reducing bullying behavior by strengthening five core competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. Additionally, the success of SEL implementation is influenced by several supporting factors, such as high levels of student empathy, the creation of a positive school climate, and the active involvement of teachers and parents. This study concludes that PSE is an effective strategy for preventing and addressing bullying in elementary schools. Therefore, it is recommended that the PSE program be adapted to incorporate Indonesian local wisdom values, and that longitudinal research be conducted to assess the sustainability of its implementation effects.